Online energy-efficient node selection algorithm for cooperative sensing in cognitive radio networks - Wei YANG; Dong-lin GUAN; Dong-hui LU; Li-hong PENG; Wen-hua DOU (Tongxin xuebao)
To meet the requirement of the energy-efficient cooperative sensing applications in cognitive radio networks,the energy minimization node selection (EMNS)and the online energy-efficient node selection (OENS) problems were proposed,for one round and online cooperative sensing scenarios,respectively.Both problems were proved to be NP-hard.For EMNS,first a branch and bound algorithm BAB was proposed to find the optimal solution,then a greedy selection algorithm GS was designed to get a heuristic solution.For OENS,based on algorithms BAB and GS,two online algorithms OBAB and OGS1 were proposed,in which the weight coefficients were adopted that consider the load balancing of each node’s energy consumption.Extensive experiments by simulations demonstrate that the proposed algorithms can significantly increase the number of successful cooperative sensing processes,thereby increasing the network lifetime effectively.